Effects of oxygen during long-term hypothermic machine perfusion in a porcine model of kidney donation after circulatory death - Venema, L; Brat, A; Moers, C; 'T Hart, N; Ploeg, R; Hannaert, P; Minor, T; Leuvenink, H; Cope Consortium (Lippincott, Williams and Wilkins, 2019)
Background: Hypothermic machine perfusion (HMP) has become standard care in many center’s to preserve kidneys donated after circulatory death (DCD). Despite a significant reduction in metabolism at low temperatures, remaining cellular activity requires oxygen. Since the role and safety of oxygen during HMP has not been fully clarified, its supply during HMP is not standard yet. This study investigates the effect of administering oxygen during HMP on renal function in a porcine DCD model. Methods: After 30 minutes of warm ischemia, porcine slaughterhouse kidneys were preserved for 24 hours by means of cold storage (CS), or HMP with Belzer Machine Perfusion Solution (UW- MPS) supplemented with no oxygen, 21% or 100% oxygen. Next, kidneys were reperfused for 4 hours in a normothermic machine perfusion (NMP) setup. Results: HMP resulted in significantly better kidney function during NMP. Thiobarbituric acid-reactive substances (TBARS), markers of oxidative stress, were significantly lower in HMP preserved kidneys. HMP preserved kidneys showed significantly lower ASAT and LDH levels compared to kidneys preserved by CS. No differences were found between the HMP groups subjected to different oxygen concentrations. ATP levels significantly improved during HMP when active oxygenation was applied. Conclusion: This study showed that preservation of DCD kidneys with HMP is superior to CS. Although the addition of oxygen to HMP did not result in significantly improved renal function, beneficial effects were found in terms of reduced oxidative stress and energy status. Oxygen addition proofed to be safe and did not show detrimental effects.